Liver/Fegato (C22.0) - Double metachronous cutaneous metastases from recurrent hepatocellular carcinoma: a case report /Metastasi cutanea da carcinoma epatocellulare recidivo: presentazione di un caso clinico - Racca, P.; Mistrangelo, M.; Spadi, et al., R. (European Journal of Oncology and Environmental Health, 2013)
Cutaneous metastases from hepatocellular carcinoma (HCC) are rare. We report an unusual case of metachronous double skin metastases to the left nostril and the buttocks in a patient with HCC. The lesions were discovered during clinical and radiological follow-up and appeared as solitary, painless, reddish-blue nodules that bleed easily, prompting suspicion of metastatization of HCC to the nose. This is the fourth reported case of cutaneous skin metastasis to the nose. Besides the highly unusual skin sites, another  peculiarity of this case is the long survival of the patient, given that the survival rate after a diagnosis of HCC is generally about 5 months. The clinical course and histopathology are compared with other similar cases. This case suggests that skin metastasis in patients with HCC who present with skin nodules should be included in the differential diagnosis of lesions arising in unusual localizations.Metastasi cutanea da carcinoma epatocellulare recidivo: presentazione di un caso clinicoLe metastasi cutanee da carcinoma epatocellulare (CE) sono rare.  Riportiamo un insolito caso di metastasi cutanee metacrone insorte contemporaneamente in due sedi differenti: narice sinistra del naso e  sede glutea in un paziente affetto da CE. Le lesioni sono state evidenziate durante il follow-up clinico-radiologico e apparivano isolate, asintomatiche, in forma di noduli rosso-blu facilmente sanguinanti, ponendo il sospetto di metastatizzazione di CE al naso. Questo è il quarto caso riportato in letteratura di metastasi cutanee al naso. Oltre alla sede cutanea, decisamente poco comune, un’altra peculiarità di questo report è la lunga sopravvivenza del paziente, dal momento che il tasso di sopravvivenza dopo una diagnosi di CE metastatico è generalmente di circa 5 mesi. L’evoluzione clinica ed istopatologica sono state confrontate con altri casi simili. Questo caso suggerisce che le metastasi cutanee in pazienti con CE che presentano noduli cutanei dovrebbero essere incluse nella diagnosi differenziale di lesioni che insorgono in sedi inusuali.